Culture of the School Literacy Movement (GLS) for Students in Elementary Schools to Realize the 2045 Golden Generation - Lisa Retnasari; Dewi Setyaningrum; Danang Prasetyo (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2022)
This study aims to analyze the culture of the School Literacy Movement (GLS) in elementary school students to realize the 2045 golden generation. This study uses a descriptive method with a qualitative approach. The subjects of this study consisted of principals, teachers, school committees, and students. Data collection techniques using interviews, observation, and document review. Data analysis techniques were carried out by collecting data, reducing data, presenting, and drawing conclusions. The results of the study indicate that the educational environment at the Lempuyangwangi State Elementary School views literacy culture as an activity that is more than just reading books, but also includes a wider scope of literacy such as mathematical literacy and technological literacy. The GLS cultural program consists of writing guidance, activity competitions to visit the library, literacy celebrations, reading halls, reading in the library, and literacy corners. The success of GLS is supported by good cooperation. Cooperation within internal schools, schools with committees and schools with parents of students. Communication forums are established through regular meetings and two-way parent associations. Availability of literate human resources and physical infrastructure that supports GLS culture. Monitoring and evaluation are regularly carried out to see the progress of the GLS culture.